Abundance and characterization of microorganisms isolated from oil palm empty fruit bunches waste under aerobic, anaerobic, and facultative anaerobic conditions - DERMIYATI DERMIYATI; RADIX SUHARJO; MARELI TELAUMBANUA; RULLY YOSITA; ANGGI WINANDA SARI; ANIS PUJI ANDAYANI (Society for Indonesian Biodiversity, 2020)
Abstract. Dermiyati, Suharjo R, Telaumbanua M, Yosita R, Sari AW, Andayani AP. 2020. Abundance and characterization of microorganisms isolated from oil palm empty fruit bunches waste under aerobic, anaerobic, and facultative anaerobic conditions. Biodiversitas 21: 4213-4220. Increased production of palm oil causes an increase in oil palm empty fruit bunches waste, while the utilization of the waste has not been carried out optimally. Oil palm empty fruit bunches contain high cellulose content which promotes the development of various types of bacteria with different characteristics. This study was aimed to determine the abundance and the characterization of bacteria that were isolated from extract suspension of oil palm empty fruit bunches in the form of a local microorganism solution under aerobic, anaerobic, and facultative anaerobic conditions. For isolation, the oil palm empty fruit extract suspension was inoculated on media Plate Count Agar Peptone and bacterial abundance was determined. Various bacterial characterization test included bacterial morphology test in the form of color and shape of macroscopic isolates, gram test using KOH 3%, fermentative oxidative test, soft rot test on potato tubers, hypersensitivity test on tobacco plant leaves, and hypo virulent test which was indicated by the presence of symptoms of disease in cucumber sprouts and indicated in the disease severity index (DSI) was carried out. The results of local microorganism solution isolation from oil palm empty fruit bunches obtained as many as 220 bacterial isolates consisting of 84 isolates in aerobic condition, 68 isolates in anaerobic condition, and 68 isolates in facultative anaerobic condition. The highest bacterial abundance in aerobic conditions was equal to 285.60 x 1010 CFU mL-1. Each bacterial isolate had different characteristics. Most of the characteristics of bacteria were turbid white (34.55%), round (69.55%), gram-positive (76.36%), fermentative (89.55%), softrot negative (71.82%), hypersensitive negative (97.27%), and virulent (74.55%).